Factors influencing service innovation of MSNs in China: a theoretical and empirical research. Issue 3 (18th September 2017) - Zhao, Yang; Zhou, Ruoxin; Ci, Yinping
Abstract : Purpose: The purpose of this paper is to explore the key factors influencing the service innovation of mobile social networks (MSNs), figure out the mechanism of all factors in different stages of service innovation and help mobile social application developers promote better service innovation. Design/methodology/approach: From previous research, this paper adopted nine initial factors that influence the service innovation of MSNs, and divide the service innovation process into three stages (i.e. demand analysis, service design and innovation implementation). On that basis, the authors constructed a model, and then collected data from 184 managers from 20 leading MSN corporates in China through questionnaires to examine the model. Furthermore, factor analysis was used to extract key factors influencing the service innovation of MSNs, correlation analysis was employed to discuss the relationship among factors and regression analysis was applied to explore their specific roles in different stages in the service innovation process. Findings: The empirical results show that the service innovation of MSNs is mainly influenced by five key factors: user, developer, market environment, social environment and technology. The authors found that different factors played remarkably different roles in the three stages. In specific, all factors but technology are important in the demand analysis stage; all factors but social environment are critical to service design; and all factors but user contribute to the implementation of service innovation. Practical implications: The results of this study can help mobile social application developers and mobile social service providers in China to better understand the driving force of service innovation and what should be emphasized in different stages, and then find the optimal path to implement service innovation, improve their service quality and user experience and facilitate the development of Chinese MSNs. Originality/value: This is the first research that comprehensively explores factors influencing the service innovation of Chinese MSNs from multi-dimensional perspectives, which provides profound theoretical guidance to the practice of service innovation in China. Also, it contributes to the development of innovation theory of traditional web services.